HUBUNGAN MUTU PELAYANAN DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP RUMAH SAKIT TENTARA PEKANBARU - Jihan Natassa; - Afrizah (Sistem Informasi, 2017)
Satisfaction beginning of the acceptance of the patient first came to the patient leaves the hospital (Herlambang, 2016). Four-level military hospital pekanbaru 01.07.04 has a fundamental duty to implement health care outpatient and inpatient, where the value BOR 25,08 %, Initial surveys are known to many complain to the patients so that they are less satisfied. Intention of this research is what is there is relationship quality of care and patient’s satisfactioninpatient unit four level military hospital Pekanbaru 2016. This Research method is analytic quantitative with research desain use transversal crosscut approach (sectional cross) its responder is patients inpatient in the mounth of May until June 2016.This Research Sample counted 87 people patients inpatient. Technique intake ofsample isnon probability sampling. Analysis the used is analysis of univariat bivariate and with test of Chi-Square, measure instrument the used is data processing and questionnaires use computerization. Result of research show there are relation between reability (Value P 0,003,value of OR=4,313), assurance (Value P 0,034, value of OR=2,833),tangibles (Value P 0,006, value of OR=3,882), emphaty (Value P 0,022, value of OR=3,257), responsiveness (Value P 0,003,value of OR=4,308) with patient satisfaction in the inpatient unit four level military hospital Pekanbaru 2016. Suggested to the relevan agencies, namely the military hospital to improve the quality of services provided to inpatient through training to health workers.